THE IDENTIFICATION OF PURCHASE INTENTION AMONG IPHONE CUSTOMERS IN DEPOK VIEWED FROM EWOM, BRAND IMAGE, BRAND TRUST, PERCEIVED VALUE, AND BRAND PREFERENCE - Ruslim, Tommy Setiawan; Nova, Nova; Herwindiati, Dyah Erny; Cokki , Cokki (International Journal of Application on Economics and Business, 2023)
Communication has become a kind of activities performed by human beings everyday, either directly or indirectly. Handphone as one among the communication means, was then developed into smartphone. Due to many smartphones released every year, customers are then faced with so many choices. One among the global reputable smartphone brands is Apple. Therefore, Apple sellers must be able to attract the customers’ attention and increase their purchase intention toward iPhone products, so that these products can compete with others and survive in the market. This research aimed to test the effects of EWOM, brand image, brand trust, perceived value, and brand preference on purchase intention among iPhone customers in Depok, West Java, Indonesia. This descriptive research was conducted to depict the characteristics or functions of a population. By using questionnaire distributed online and among 355 respondents filling-out, there were only 349 respondents from which the data can be processed further by using the SmartPLS-SEM software. The result of this research supported that brand image, brand trust, perceived value, and brand preference have positive and significant effects on purchase intention among iPhone customers in Depok, while EWOM does not have significant effect on purchase intention.